2000
DOI: 10.1246/cl.2000.1086
|View full text |Cite
|
Sign up to set email alerts
|

Active Species of Molybdenum Carbide Catalysts in Methane Reforming: η-Mo3C2

Abstract: η-Mo3C2 was the most active molybdenum carbide species for methane reforming, surpassing β-Mo2C which has been reported previously. From the correlation of the TPR results, the amount of η-Mo3C2 was directly related to the methane decomposition rate, indicating the importance of this type of carbide for methane reforming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Also, the structure of the carbide catalyst can be tailored by changing the preparation procedures and conditions. [10][11][12] The structures and properties of different molybdenum carbide and oxide materials have been studied and described. 13 To date, the transition metal carbide materials are rarely used in industrial applications, as more work is needed to improve the surface area of the bulk carbides and to develop new methods to prepare supported carbide catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the structure of the carbide catalyst can be tailored by changing the preparation procedures and conditions. [10][11][12] The structures and properties of different molybdenum carbide and oxide materials have been studied and described. 13 To date, the transition metal carbide materials are rarely used in industrial applications, as more work is needed to improve the surface area of the bulk carbides and to develop new methods to prepare supported carbide catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these materials has attracted considerable attention over the last fifteen years and a number of routes have been developed, of which temperature programmed reaction (TPRe) of the metal oxide with methane has been the most common. [1][2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19] Relatively few studies have been carried out on the preparation of molybdenum carbide with other carbon sources. 17,18 Particularly amongst the hydrocarbons, there are a myriad of possible carbon sources for carburisation.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles have been published to investigate the effect of the crystal structure on catalytic activity in DRM [78,217]. Liang et al [78] investigated the catalytic activity of β-Mo 2 C and α-MoC 1-x phases in DRM.…”
Section: Molybdenum Carbidementioning
confidence: 99%
“…Better activity was observed for the -MoC 1-x phase. Oshikawa et al [217] observed the dependence of the η-Mo 3 C 2 phase on the methane decomposition rate. They reported the key role of the η-Mo 3 C 2 phase among other molybdenum carbide phases as an active species for methane reforming.…”
Section: Molybdenum Carbidementioning
confidence: 99%
“…temperatures (Claridge et al, 1998;Brungs et al, 2000;Oshikawa et al, 2000;Tsuji et al, 2000;Shamsi and Lyons, 2000). These groups have primarily focused on preparation and testing of the catalytic activity of molybdenum and tungsten carbide catalysts, as well as characterization and some mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%